2011
DOI: 10.1111/j.1365-2133.2010.10107.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased arterial stiffness in patients with psoriasis is associated with active systemic inflammation

Abstract: Young patients with psoriasis have increased arterial stiffness but not microvascular dysfunction compared with healthy controls. More importantly, hs-CRP positively correlated with, and independently predicted, arterial stiffness. This suggests that systemic inflammation in patients with psoriasis is associated with premature atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
80
3
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(101 citation statements)
references
References 20 publications
13
80
3
4
Order By: Relevance
“…The findings of present study correlate well with findings of previous studies -Pereira et al (2004) [5], Coimbra et al (2009) [15], Yiu et al (2011) [16] and Lucy Piper et al (2012) [4].…”
Section: Increased C -Reactive Protein Levelssupporting
confidence: 93%
“…The findings of present study correlate well with findings of previous studies -Pereira et al (2004) [5], Coimbra et al (2009) [15], Yiu et al (2011) [16] and Lucy Piper et al (2012) [4].…”
Section: Increased C -Reactive Protein Levelssupporting
confidence: 93%
“…It has been suggested that the inflammatory process in psoriasis, which is characterized by elevated levels of CRP, is connected to increased arterial stiffness and premature development of atherosclerosis. These findings provide further evidence of a link between inflammation and cardiovascular diseases in patients with psoriasis [220]. This study is consistent with the research published by Ludwig et al [221], which reported an increased prevalence and severity of coronary artery calcification as an indicator for cardiovascular disease in patients with psoriasis.…”
Section: C-reactive Protein (Crp)supporting
confidence: 93%
“…Considering these results, the authors suggested that in psoriasis there might be an inflammatory process which persists even after the therapy, and may lead to the development of atherogenic changes [219]. A positive correlation between elevated serum levels of high sensitivity of CRP (hs-CRP) and the degree of arterial stiffness in patients with psoriasis was reported in another study [220]. Moreover, increased concentration of hs-CRP seems to be an independent predictor of arterial stiffness.…”
Section: C-reactive Protein (Crp)mentioning
confidence: 89%
“…23,24 Uma das técnicas utilizadas para a sua avaliação é a medição da velocidade da onda de pulso (VOP) arterial, definida pela distância percorrida pelo fluxo sanguíneo dividida pelo tempo que esta leva a percorrer essa distância (m/s). 23 Yiu et al 25 verificaram que a VOP braquial-tornozelo (VOP b-t ) nos doentes com psoríase estava significativamente aumentada quando comparada com a dos indivíduos saudáveis do mesmo sexo e idade. Para além disso mostraram que, nos doentes psoriáticos, existia uma correlação positiva entre a VOP b-t e a idade.…”
Section: Ateroscleroseunclassified